A study on the psychological needs of nurses caring for patients with coronavirus disease 2019 from the perspective of the existence, relatedness, and growth theory - Xue Yin; Lingdan Zeng (Elsevier, 2020)
Objective: This study aimed to explore the psychological needs of nurses caring for patients with coronavirus disease 2019(COVID-19) and to propose corresponding interventions. Methods: In-depth interviews were conducted with 10 nurses who cared for patients with COVID-19. Interview data were analyzed by category analysis from the perspective of the existence, relatedness, and growth theory (ERG). Results: The existence needs were mainly reflected in health and security needs, whereas the relatedness needs consisting mainly of interpersonal needs, humanistic concern needs, and family needs; further, the growth needs were mainly reflected as a strong need for knowledge. Existence needs were the main needs during the epidemic, with health and security needs influencing each other. Humanistic concern needs were the most important of the relatedness needs; interpersonal and family needs were also growing. Conclusion: It is found that the existence, relatedness, and growth needs coexist in clinical nurses. It is helpful to take effective interventions to meet their needs if the needs of nurses caring for COVID-19 patients could be perceived well.